2019
DOI: 10.2147/tcrm.s206147
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictors of postoperative outcomes in infants with low birth weight undergoing congenital heart surgery: a retrospective observational study</p>

Abstract: Background Despite improvements in neonatal cardiac surgery and postoperative care, hospitalized death for infants with low birth weight remains high. Objective This study sought to identify predictors of postoperative outcomes in low-birth-weight infants undergoing congenital heart surgery and establish nomograms to predict postoperative intensive-care unit (ICU) stay. Methods From June 2009 to June 2018, a retrospective review of 114 infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…In many cases, the disorder is caused by damage of brain during surgery. The incidence of neurological disorders in some studies was in range of 4-15% [12,17]. In our study the incidence of postoperative clinical seizures was 6.6%.…”
Section: Discussionsupporting
confidence: 48%
“…In many cases, the disorder is caused by damage of brain during surgery. The incidence of neurological disorders in some studies was in range of 4-15% [12,17]. In our study the incidence of postoperative clinical seizures was 6.6%.…”
Section: Discussionsupporting
confidence: 48%
“…However, we observed that a weight ≤ 3.75 kg during the operation predicted the incidence of postoperative LCOS in the ROC and AUC analyses. Lu et al ( 34 ) found that a low operation weight was a significant risk factor for mortality in infants with congenital heart defects in a Chinese population. Therefore, we suggest that if there are no other factors indications for emergency surgery, body weight should be increased by strengthening nutrition, which could help reduce the incidence of postoperative LCOS.…”
Section: Discussionmentioning
confidence: 99%
“…This nomogram was constructed using the training cohort and achieved good performance in both the training and validation cohorts; the ROC and C-index results were also good in both cohorts. Nomogram is a very useful tool to predict diseases or outcomes ( Gu et al, 2020 ; Kong et al, 2019 ; Lei et al, 2016 ; Li & Meng, 2019 ; Lu et al, 2019 ). The nomogram constructed in this study had good predictive performance and generalizability.…”
Section: Discussionmentioning
confidence: 99%